1993
DOI: 10.1007/bf01957227
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis: The ΔF508 mutation does not lead to an exceptionally severe phenotype. A cohort study

Abstract: In an attempt to ascertain a relationship between genotype and phenotype, we studied the pulmonary and nutritional status of 123 cystic fibrosis patients with known genotype at an age of 8.5-10 years. Patients represent a cohort as they are almost all those born and diagnosed in a given area and period. They were followed at a single centre using uniform diagnostic and treatment protocols. Pulmonary and nutritional status of homozygous delta 508 patients did not differ from that of compound heterozygotes or of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 27 publications
0
20
0
1
Order By: Relevance
“…Homozygotes for ∆F508 mutation have been found to have a greater incidence of pancreatic insufficiency, worse lung function and higher mortality compared to other genotypes [2,3] while isolated mutations such as A455E are associated with a mild clinical course [4]. However, a cohort study in Italy showed that pulmonary status in 8.5-10 yr old ∆F508 homozyotes was no different from that in other mutations [5]. Indeed, the conclusion from a large phenotype genotype consortium [6] was that the only prognostic value of genotypic information is for the prediction of pancreatic sufficiency.…”
mentioning
confidence: 98%
“…Homozygotes for ∆F508 mutation have been found to have a greater incidence of pancreatic insufficiency, worse lung function and higher mortality compared to other genotypes [2,3] while isolated mutations such as A455E are associated with a mild clinical course [4]. However, a cohort study in Italy showed that pulmonary status in 8.5-10 yr old ∆F508 homozyotes was no different from that in other mutations [5]. Indeed, the conclusion from a large phenotype genotype consortium [6] was that the only prognostic value of genotypic information is for the prediction of pancreatic sufficiency.…”
mentioning
confidence: 98%
“…Studies focusing on pulmonary status as a function of the Δ508del allele have reported a wide range of effects, from a detectable impact of CFTR genotype to no or statistically insignificant influences [34,35]. Other studies using more refined assessment of CFTR mutations have shown statistically significant correlations between CFTR genotypes and pulmonary status, whereas still others have failed to detect a significant association [36].…”
Section: Discussionmentioning
confidence: 99%
“…KEREM et al [5] showed that ∆F508 homozygotes almost always have pancreatic insufficiency, whereas 28% of ∆F508 compound heterozygotes and 64% of patients who do not carry a ∆F508 mutation have adequate pancreatic function. In contrast, no correlation was found between the ∆F508 genotype and pulmonary status [5][6][7][8][9][10][11]. In the majority of studies [5,6,8,9,11], the lack of correlation between genotype and pulmonary status might, in part, be explained by selection of young patients (mean age ranging 9-18 yrs), which may give insufficient background to assess the long-term outcome of pulmonary involvement.…”
mentioning
confidence: 99%
“…In contrast, no correlation was found between the ∆F508 genotype and pulmonary status [5][6][7][8][9][10][11]. In the majority of studies [5,6,8,9,11], the lack of correlation between genotype and pulmonary status might, in part, be explained by selection of young patients (mean age ranging 9-18 yrs), which may give insufficient background to assess the long-term outcome of pulmonary involvement. In two studies which focused on CF adult patients only [7,10], and in most other studies [5,6,8,9], comparison between homozygotes or compound heterozygotes for the ∆F508 mutation were made without differentiating compound heterozygotes according to the type of their non-∆F508 mutation, which may influence the severity of the pulmonary outcome.…”
mentioning
confidence: 99%
See 1 more Smart Citation